STUDY OF BETRAYAL ANALYSIS IN THE QURANIC PERSPECTIVE - Septian, Tomi; Ghafar, Abdul; Dja'far, Halimah (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2023)
The concept of betrayal from the perspective of the Qur'an emphasizes the forms of betrayal and the implications of the verses offered by the Qur'an in dealing with these acts of betrayal. The objectives of this research include three, namely, knowing the terms related to betrayal. Second, know the forms and factors that cause betrayal. Third, know solutions to prevent treasonous acts. This research uses a qualitative analysis method, collecting data from Al-Quran verses related to betrayal. Data was analyzed using a textual and contextual approach to understand the meaning, context, and message conv, eyed by the Al-Quran regarding treasonous acts. The data analysis technique used in this research is the qualitative analysis based on the views of the Book of Tafsir Al Misbah by Prof. Quraish Shihab, Tafsir Ibnu Katsir, and Tafsir, Kemenag. The results of this research show that the terms of betrayal that can be identified are munafiq, murtad, disobedient, ghulul, kadzib, and the factors that cause traitorous behavior include hubb, hasad, khasam, baghyu, and anniayah.